Melt volume flow rate and melt flow rate of kenaf fibre reinforced Floreon/magnesium hydroxide biocomposites - Lee, Ching Hao; Salit, Mohd Sapuan; Lee, J. H.; Hassan, Mohd Roshdi (SpringerOpen, 2016)
A study of the melt volume flow rate (MVR) and the melt flow rate (MFR) of kenaf fibre (KF) reinforced Floreon (FLO) and magnesium hydroxide (MH) biocomposites under different temperatures (160–180 °C) and weight loadings (2.16, 5, 10 kg) is presented in this paper. FLO has the lowest values of MFR and MVR. The increment of the melt flow properties (MVR and MFR) has been found for KF or MH insertion due to the hydrolytic degradation of the polylactic acid in FLO. Deterioration of the entanglement density at high temperature, shear thinning and wall slip velocity were the possible causes for the higher melt flow properties. Increasing the KF loadings caused the higher melt flow properties while the higher MH contents created stronger bonding for higher macromolecular chain flow resistance, hence lower melt flow properties were recorded. However, the complicated melt flow behaviour of the KF reinforced FLO/MH biocomposites was found in this study. The high probability of KF–KF and KF–MH collisions was expected and there were more collisions for higher fibre and filler loading causing lower melt flow properties.